2012
DOI: 10.1021/jp301714z
|View full text |Cite
|
Sign up to set email alerts
|

Xylene-Capped Luminescent Silicon Nanocrystals: Evidence of Supramolecular Bonding

Abstract: We report capping of silicon (Si) nanocrystals (NCs) via xylene attachment to the surface of oxide etched, luminescent, core/shell nanostructures of Si/Si-oxide in colloidal suspension. The core/shell nanostructures of Si/Si-oxide are formed by controlled oxidation of mechanically milled crystalline Si, which is subsequently etched in aqueous hydrofluoric acid to remove the oxide shell. Xylene attachment is confirmed by peak splitting and shifting in the Fourier transform infrared spectra for the xylene-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The CIE coordinates of the fabricated white LED closely match with the pure white light (0.33, 0.33). The performance and color purity of the orange luminescent perovskite-coated white LED are comparable or better than the other reported orange luminescent phosphor-coated white LEDs using carbon dots, silicon dots, and other 2D materials. Hence, the mixed halide perovskite can be considered as a promising candidate for the high color quality, low-cost white light production, and in the solid-state lighting field. The operational stability of fabricated LED is measured up to 7 h of continuous operation at 2.35 V. It is observed that the intensity of blue emission from LED chip (encapsulated) is nearly unchanged, while the intensity of yellow emission from MAPbBr 1 I 2 is decreased by about 20%, as shown in Figure S8b (Supporting Information).…”
Section: Resultsmentioning
confidence: 75%
“…The CIE coordinates of the fabricated white LED closely match with the pure white light (0.33, 0.33). The performance and color purity of the orange luminescent perovskite-coated white LED are comparable or better than the other reported orange luminescent phosphor-coated white LEDs using carbon dots, silicon dots, and other 2D materials. Hence, the mixed halide perovskite can be considered as a promising candidate for the high color quality, low-cost white light production, and in the solid-state lighting field. The operational stability of fabricated LED is measured up to 7 h of continuous operation at 2.35 V. It is observed that the intensity of blue emission from LED chip (encapsulated) is nearly unchanged, while the intensity of yellow emission from MAPbBr 1 I 2 is decreased by about 20%, as shown in Figure S8b (Supporting Information).…”
Section: Resultsmentioning
confidence: 75%
“…32 Post-synthesis surface engineering of Si-ncs has so far largely relied on traditional or enhanced (e.g. thermally, by illumination) solution chemistry 33,73,[75][76][77][78][79][80][81] and only very recently, alternative approaches have made signicant and very promising advances. 17,22,23,75,[82][83][84][85][86][87][88][89] The solution chemistry approach is generally achieved through the realization of a chemically active surface (e.g.…”
Section: Introduction To Si-nc Surface Engineeringmentioning
confidence: 99%
“…In recent times, luminescent silicon QDs (Si QDs) have been considered highly attractive for LEDs because they are considered to be nontoxic, photostable, conductive, and involve environmental-friendly nanomanufacturing. [115][116][117] Towards this end, exploitation of light emission from nanostructured Si and the improvement of the optical properties are very important.…”
Section: Silicon Qd-based White Ledsmentioning
confidence: 99%